Predictive Effect of GDF-15 on Adverse Outcomes After Cardiovascular Interventions: A Systematic Review and Meta-Analysis - Xiaotong Jia; Junwei Gao; Zeyou Qi; Jun Ma (Reviews in Cardiovascular Medicine)
Background: This systematic review and meta-analysis aimed to evaluate the predictive effect of Growth Differentiation Factor-15 (GDF-15) on adverse outcomes in patients undergoing cardiovascular interventions. Method: A comprehensive literature search was performed across PubMed, EMBASE, Cochrane Library, and Web of Science databases. The meta-analysis used hazard ratios (HR) and odds ratios (OR) to compare outcomes such as all-cause mortality, cardiovascular death, postoperative atrial fibrillation (AF), acute kidney injury (AKI), and spontaneous myocardial infarction (MI) between high GDF-15 levels and control groups. Subgroup analyses were conducted based on study design and GDF-15 cutoff levels. Publication bias was evaluated using funnel plot and Egger’s test. Results: A total of 13 studies were included in the meta-analysis. The study revealed a significant association between elevated GDF-15 levels and increased all-cause mortality. Subgroup analysis showed a significant association in retrospective studies but not in prospective studies. Higher GDF-15 cutoff levels (>2 ng/mL) were more strongly associated with increased mortality than lower cutoff levels (≤2 ng/mL). Elevated GDF-15 levels were found to be significantly associated with increased risks of cardiovascular death, AKI, and spontaneous MI. No significant difference was observed in the incidence of postoperative AF. The overall adverse outcomes analysis showed no significant difference. Subgroup analyses suggested significant associations primarily observed in studies with higher GDF-15 cutoffs. Conclusion: Elevated GDF-15 levels are associated with increased risks of all-cause mortality, cardiovascular death, AKI, and spontaneous MI in patients undergoing cardiovascular interventions. Due to the heterogeneity of the studies, including variations in surgical techniques, the conclusions should be interpreted with caution. The PROSPERO Registration: CRD42024582279, https://www.crd.york.ac.uk/PROSPERO/view/CRD42024582279.